1939
DOI: 10.1021/ja01873a020
|View full text |Cite
|
Sign up to set email alerts
|

Sterols. LIII. The Structure of the Side Chain of Sarsasapogenin

Abstract: A study has been made of the behavior of certain aliphatic organic acids chiefly typical hydroxy, unsaturated, or keto, toward reduction catalyzed by Raney nickel and in the presence of sodium hydroxide and under high hydrogen pressure.2. At temperatures below 250°and hydrogen pressures not exceeding 330 atmospheres, a-and -hydroxy acids are not affected, whereas ß-hydroxy acids are converted into the corre-sponding unsubstituted acids.3. The unsaturated acids studied were hydrogenated rapidly at temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1951
1951
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…and 22-isoallospirostan-3/3-ol (tigogenin) (Ha). Since this first observation already was in complete contrast to Marker's report (2), 22-isoallospirostan-3j8-ol (Ha), 22-isoallospirostan (desoxytigogenin) (lib) (6) and 22-isoallospirostane-3|S, 12diol 3,12-diacetate (lie) (rockogenin) were similarly brominated, but in this instance only a 23-monobromo derivative was formed. From these observations it appears that the steroidal sapogenin side chain can be dibrominated in the normal (neo) configuration, but only monobrominated when it possesses the 22-iso configuration.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…and 22-isoallospirostan-3/3-ol (tigogenin) (Ha). Since this first observation already was in complete contrast to Marker's report (2), 22-isoallospirostan-3j8-ol (Ha), 22-isoallospirostan (desoxytigogenin) (lib) (6) and 22-isoallospirostane-3|S, 12diol 3,12-diacetate (lie) (rockogenin) were similarly brominated, but in this instance only a 23-monobromo derivative was formed. From these observations it appears that the steroidal sapogenin side chain can be dibrominated in the normal (neo) configuration, but only monobrominated when it possesses the 22-iso configuration.…”
mentioning
confidence: 70%
“…Chem., preceding paper. 2 The conversion of A5-22-isospirosten-3;3-ol-12-one (botogenin) to A5-pregnen-30,17adiol-12,20-dione has been reported by Marker (J. Am.…”
mentioning
confidence: 91%
“…(b) Acid-catalyzed isomerization: Two other acid catalyzed reactions have been observed for sapogenins and have some relevance for SGAs. Marker and Rohrmann [101] found that sarsasapogenin (21) on being refluxed with alcoholic HCl yielded smilagenin (22) (Figure 13). Wall et al [102] established that the reaction is reversible and both compounds give a mixture containing approximately 20% sarsasapogenin and 80% smilagenin.…”
Section: Formation Of Artifactsmentioning
confidence: 99%
“…Originally identiÐed as C 26 compounds, they were revised to in 1935, 3 and their C 27 side-chains were correctly identiÐed by chemical analysis in 1939. 4 Smilagenin, (25a f )-5b-spirostan-3b-ol (1), and sarsasapogenin, (2), (25b f )-5b-spirostan-3b-ol are stereoisomers di †ering in conÐguration at C-25. Smilagenin is the 25R (25D) form and sarsasapogenin the 25S (25L) form.…”
Section: Introductionmentioning
confidence: 99%